2017
DOI: 10.20944/preprints201711.0141.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stability and Flexibility of the Organizational Culture after the Transition of Economy—The Case of Serbia

Abstract: The main goal of this paper is to address how quickly and to what extent are international organizational cultures, brought by the world companies after the process of privatization, being implemented in a single monolithic culture. For this purpose was adopted and applied Denison model of organizational culture, which has been chosen because it emphasizes the need for balance between requirements for organization’s stability demands and its required flexibility. Considering that a different organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The research found out that staff on hotels cared most about job stability since it was linked to higher levels of organizational commitment. This result is agreed with Cicek and Kiyak, 2011;Omega, 2012;Kirin, et al, 2017;Sears, 2021) indicated that organizations that focus on the stability of employees get a lot of benefits, including the dedication and commitment of the employees in the hotel. the second hypothesis Innovation is positively impact to organizational commitment.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The research found out that staff on hotels cared most about job stability since it was linked to higher levels of organizational commitment. This result is agreed with Cicek and Kiyak, 2011;Omega, 2012;Kirin, et al, 2017;Sears, 2021) indicated that organizations that focus on the stability of employees get a lot of benefits, including the dedication and commitment of the employees in the hotel. the second hypothesis Innovation is positively impact to organizational commitment.…”
Section: Discussionsupporting
confidence: 84%
“…Omega (2012) mentioned that stability assesses the firm's predictability and rule. Gavic et al, (2017) stated that an organization needs stability as much as anything else, and stable organizations survive crises. Sears (2021) added that stability had a substantial impact on employee commitment, when employees' stability was high the strongest commitment was detected; when employees' stability was poor commitment was clearly weaker.…”
Section: 21: Stabilitymentioning
confidence: 99%
“…The fourth dimension is stability an expression refers to the employee stability of a job in any organizations (Vucetic and Milosevic 2017). stability is equally vital for an organization; and stable organizations endure in times of crisis (Kirin et al, (2017). The fifth -dimension emphasis on reward is very important in all organization, it is in charge of human attitude inside any organization (Trivedi 2015).…”
Section: Organizational Culture Dimensionmentioning
confidence: 99%